Transformation of PAI Learning Through Approaches to Active Deep Learning Experience (ADLX) In The Digital Era - Ahmad Munadirin; Muslim, Rifqil; Fatah, Zainal (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2023)
Islamic Religious Education (PAI) learning often encounters negative perceptions among students. This is because the learning model used is still conventional, resulting in a rigid and monotonous perception. Therefore, an adaptation using an innovative learning model is needed in order to attract student participation during the learning process. This study aims to examine more deeply the transformation of PAI learning using the model Active Deep Learner Experience (ADLX) and find out how it impacts Islamic Religious Education learning. Using the literature study method, the author collects sources from accredited journals as primary data in the study and analyzes them using content analysis. The results of the study indicate that the ADLX model is able to provide a significant impact in various aspects, including critical reasoning, character development, learning motivation, student involvement, academic achievement, and technology utilization. Not only that, the use of the ADLX model is able to change the direction of negative perceptions towards active and innovative Islamic Religious Education learning. This study is still limited to literature analysis without involving empirical testing in the field. For this reason, further research is needed to explore more deeply the implementation of the ADLX model in various educational institutions.